Experimental Estimation of Critical Buckling Velocities for Conservative Pipes Conveying Fluid - Mohsen J. Jweeg (Al-Khwarizmi College of Engineering – University of Baghdad, 2018)
Conservative pipes conveying fluid such as pinned-pinned (p-p), clamped–pinned (c-p) pipes and clamped-clamped (c-c) lose their stability by buckling at certain critical fluid velocities. In order to experimentally evaluate these velocities, high flow-rate pumps that demand complicated fluid circuits must be used.